#### Answer

Answer of Part (a) = $-12$
Answer of Part (b)= $-9$

#### Work Step by Step

Part (a)
$3+(-7)+(-8)=$
$ 3-7-8=$
$-4-8=$
$-12=$
Part (b)
$[7+(-10)]+[-2+(-4)]=$
$(7-10)+(-2-4)=$
$-3+(-6)=$
$-9=$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

Answer of Part (a) = $-12$
Answer of Part (b)= $-9$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.